A new method for strake configuration design of Steel Catenary Risers - Park, K.S. (Taylor and Francis Ltd., 2016)
A number of studies of vortex-induced vibration (VIV) having important effect on the fatigue performance of riser have performed analytically as well as experimentally in the last decade. However, there are few research results on the configuration design of VIV suppression devices such as fairings, strakes, and etc. Therefore, a systematic design procedure of strake configuration (i.e., location and length) using the modal approach for steel catenary riser (SCR) is proposed in this study. The proposed method considers the dominant mode for VIV suppression through modal analysis of bare riser to find appropriate location and various design parameters are introduced to calculate appropriate length of VIV suppression devices. From the numerical example of SCR, it is shown that the required strake length from the optimal location for VIV suppression of SCR is much shorter than that of the conventional method. This is achieved by staggered strake installation at the effective location. Furthermore, no additional calculations or engineering cost are required for the proposed method, because the proposed method follows exact same analysis procedure of the conventional one except using the modal information of bare SCR obtained from initial analysis of bare SCR. Â© 2015 Taylor & Francis.